2010
DOI: 10.17221/204/2009-pse
|View full text |Cite
|
Sign up to set email alerts
|

Effect of salinity stress on mycorrhizal association and growth response of peanut infected by Glomus mosseae

Abstract: Arbuscular mycorrhiza is a mutualistic association between fungi and higher plants, and play a critical role in nutrient cycling and stress tolerance. However, much less is known about the mycorrhiza-mediated enhancement in growth and salinity tolerance of the peanuts (Arachis hypogaea L.) growing in the arid and semi-arid areas. Therefore, mycorrhizal status of Glomus mosseae in diverse salinity levels on original substrate soil conditions was investigated. Different growth parameters, accumulation of proline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Arbuscular mycorrhizal fungi (AMF) are ubiquitous as compared to other organisms inhibiting the rhizosphere. AMF enhances the plant growth and development by helping plants in the nutrient uptake and improving the rhizospheric soil health ( Linderman, 1994 ; Al-Khaliel, 2010 ). AMF improves several physiological processes in host plants including water absorption potential of plants by increasing the hydraulic conductivity of roots ( Al-Karaki and Clark, 1998 ; Ruiz-Lozano and Azcon, 2000 ; Ruiz-Lozano, 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…Arbuscular mycorrhizal fungi (AMF) are ubiquitous as compared to other organisms inhibiting the rhizosphere. AMF enhances the plant growth and development by helping plants in the nutrient uptake and improving the rhizospheric soil health ( Linderman, 1994 ; Al-Khaliel, 2010 ). AMF improves several physiological processes in host plants including water absorption potential of plants by increasing the hydraulic conductivity of roots ( Al-Karaki and Clark, 1998 ; Ruiz-Lozano and Azcon, 2000 ; Ruiz-Lozano, 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…Proline accumulation in plants may be responsive in less salt-tolerance species or to salinity and not necessarily to AMF, because many authors have reported that proline concentration increased in AMF plants compared to non-AMF plants [36]. Conversely, other authors have reported greater proline accumulations in non-AMF plants than AMF plants for example, in Ocimum basilicum L. [37] and Arachis hypogaea L. [38]. From the results, AMF could enhance eucalyptus nutrients uptake; high concentrations of nitrogen (N), Phosphorus (P) and Potassium (K) and low concentrations of Sodium (Na) were found in Gi.…”
Section: Discussionmentioning
confidence: 99%
“…albida with eucalyptus strains H4 and H8, and in Glomus sp.2 with eucalyptus strain P6. Although salinity stress decreased nutrient uptake, many studies have reported increasing salinity levels lowered N and K concentrations, for example in pepper, olive, peanut and chili [39][40][41][42]. High concentrations of K can be helpful to maintain K/Na ratio, cell osmotic potential from plays control of water relation and effects to increase photosynthetic rate.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this study has enormous evidences confirmed that the incorporation of AM fungi with tea wastes increased the adaption of the corn plant to salinity through enhancing the mean weight diameter, organic carbon content, and bacterial and fungal abundance. An improvement in soil structure can enhance the soil moisture content and water infiltration leading to perfect roots density and implications for the nutrients uptake and productivity [ 59 ]. Moreover, organic carbon can increase the plant growth by enhancing the biophysical properties of soil [ 60 , 61 , 62 , 63 , 64 ].…”
Section: Resultsmentioning
confidence: 99%